Pengabdian Masyarakan Dalam Meningkatkan Sumber Daya Manusia Guna Membangun Desa Wisata Di Bojong Koneng Kecamatan Babakan Madang Kabupaten Bogor - Fajar M. Syam; Mohamad Najib (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2024)
Community service is an activity aimed at increasing community participation in meeting the needs of life and solving problems faced by the community. This activity is part of the Village Building/Thematic Real Work Course (KKNT) program which is a form of education by providing learning experiences for students to live in the community outside the campus and directly together with the community identify potentials and deal with problems so that it is expected able to develop the potential of the village/region and formulate solutions to problems that exist in the village. The Thematic Real Work Lecture (KKNT) was carried out in the Bojong Koneng Tourism Village in the Babakan Madang District, Sukabumi Regency with a community service method that focused on several themes, namely society, education, family, entrepreneurship and the Indonesian Independence Day which was carried out for five weeks. It is hoped that this KKNT program can improve Human Resources in order to build superior villages and can stabilize the community's economy.